2013
DOI: 10.1371/journal.pone.0074176
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Major Chronic Conditions among Older Chinese Adults: The Study on Global AGEing and Adult Health (SAGE) Wave 1

Abstract: BackgroundThe likely corresponding increase in prevalence of chronic disease will be a major challenge for the health care system. Few nationwide epidemiological studies include a large enough sample of older adults to provide estimates of chronic conditions in the older adult population. This study aimed to estimate the prevalence of eight common chronic health conditions and examine socioeconomic inequalities in the diseases among older adults in China.MethodData are from SAGE-China Wave 1, including 13,157 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
86
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 23 publications
5
86
5
Order By: Relevance
“…As China is ageing rapidly, and the prevalence of NCD is increasing (54) , more targeted actions should be taken by the government to increase dissemination and uptake of mass educational messages for older Chinese people. Education programmes need to stress the importance of meeting the dietary intake recommendations of the CDG and CFP in order to prevent NCD in later life.…”
Section: Discussionmentioning
confidence: 99%
“…As China is ageing rapidly, and the prevalence of NCD is increasing (54) , more targeted actions should be taken by the government to increase dissemination and uptake of mass educational messages for older Chinese people. Education programmes need to stress the importance of meeting the dietary intake recommendations of the CDG and CFP in order to prevent NCD in later life.…”
Section: Discussionmentioning
confidence: 99%
“…13 The participants were interviewed through a face-to-face household survey. A five-stage sampling approach was applied.…”
Section: Methodsmentioning
confidence: 99%
“…The participants were randomly selected to do the interview and body check-up. 13 SAGE-China Wave 1 consisted of a total of 15,050 participants. 13 Among them, 1,671 were aged 18–49 years and 13,379 aged 50 years and older.…”
Section: Methodsmentioning
confidence: 99%
“…China is the most populous country in the world and has been experiencing a progressive increase in CVD, with recent studies showing that 30% of the population in China has ≥ 3 risk factors for CVD [2]. This effect appears to be more pronounced in urban areas where a western lifestyle has been adopted.The SAGE-China Wave 1 study in 2013 reported the prevalence of angina in those N50 years of age to be 10% [3]. These results were based upon the Rose angina questionnaire (RAQ) -a method commonly used to assess the prevalence of angina in population-based surveys.…”
mentioning
confidence: 99%
“…The SAGE-China Wave 1 study in 2013 reported the prevalence of angina in those N50 years of age to be 10% [3]. These results were based upon the Rose angina questionnaire (RAQ) -a method commonly used to assess the prevalence of angina in population-based surveys.…”
mentioning
confidence: 99%